Application of albumin‐bilirubin grade and platelet count to indocyanine green‐based criteria for hepatectomy: Predicting impaired liver function and postoperative outcomes of hepatocellular carcinoma. Issue 4 (11th June 2022) - Takamoto, Takeshi; Nara, Satoshi; Ban, Daisuke; Nagashima, Daisuke; Mizui, Takahiro; Esaki, Minoru; Shimada, Kazuaki
Abstract: Background: Applicability of the albumin‐bilirubin (ALBI) grade in preoperative decision‐making criteria based on the indocyanine green retention (ICG) test remains unclear. This study aimed to predict abnormal ICG values using standard blood tests and evaluate the impact on postoperative outcomes among patients undergoing hepatectomy for hepatocellular carcinoma (HCC). Methods: Data on 949 consecutive HCC patients undergoing curative‐intent hepatectomy between 1996 and 2014 were retrospectively assessed. A nomogram using preoperative standard blood tests was created to predict abnormal ICGR15 (>15%). Results: Three‐hundred nine patients had abnormal ICGR15. Predictors of abnormal ICGR15 included in the nomogram were: ALBI grade >1 (hazard ratio [HR]: 2.16, 95% confidence interval [CI]: 1.59–2.94), platelet count <130 000/mm 3 (HR: 2.27, 95% CI: 1.68–3.08), aspartate aminotransferase >50 (IU/L) (HR: 1.90, 95% CI: 1.29–2.81), and viral hepatitis infection (HR: 1.46, 95% CI: 1.03–2.07). The nomogram named the PLT‐ALBI score was discriminative [C‐statistics: 0.719 (0.684–0.754)], and reliable (Hosmer‐Lemeshow Chi‐Square: 9.05, p = 0.338). The higher PLT‐ALBI score was associated with a more frequent incidence of clinically relevant posthepatectomy liver failure and poor overall survival. Conclusions: The PLT‐ALBI score is applicable in distinguishing HCC patients with abnormal ICGR15. Patients with higher PLT‐ALBI score require more careful postoperative care, despite following the ICG criteria.